Newsletter Institute of Medical Molecular Biotechnology Issue 11 September 2021 / Institute of Medical Molecular Biotechnology - Universiti Teknologi MARA, Institute of Medical Molecular Biotechnology (Institute of Medical Molecular Biotechnology, 2022)
Bismillahirrahmanirrahim, I am pleased with this first bulletin of our pharmacy department, under the helm of Encik Asyraf, our drug information pharmacist with the assistance of our staffs. With this, I hope our patients and hospital team members alike could find this pharmacy bulletin to be useful & able to access excellent pharmaceutical care services from our pharmacy department.